(untitled) (SCIÉNDO INGENIUM, 2024)
The National University of Trujillo offers high quality educational services in its various programmes; due to the health crisis, the institution underwent a major change in the mode of delivery of classes, which became from face-to-face to virtual. This change forced the university population to make use of technological tools such as virtual platforms, but the process of adaptation was very difficult for everyone. Barriers such as the lack of previous culture and the complex manipulation of these systems prevented many students from continuing their studies. In order to address this problem, a study was carried out to determine the degrees of usability of virtual platforms through a heuristic evaluation method with the aim of identifying attributes that could be improved with the support of experts. In order to achieve this, the components that make the correct and simple use of these platforms possible were determined, where the student has the possibility of developing their subjects and being able to understand the use of the platform, which has intuitive characteristics. This research concluded with the evaluation of the grades for each component giving as a result a very significant level in the use of the virtual classroom E-learning.